Pengaruh Lingkungan Kerja, Komitmen Organisasi, dan Emotional Intelligence terhadap Organizational Citizenship Behavior: (Studi pada Karyawan PT Berau Karetindo Lestari Jakarta Selatan) - Sopiyatul Mukaromah; Zulvia Khalid (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Organizational citizenship behavior is an important factor for company progress, because it is voluntary behavior outside the official job description and can increase company effectiveness and efficiency. This study aims to analyze the influence of Work Environment, Organizational Commitment, and Emotional intelligence on Organizational citizenship behavior at PT Berau Karetindo Lestari South Jakarta. This research is a quantitative study with a sample size of 110 respondents. The sampling method uses probability sampling with simple random sampling technique. Data was collected through a questionnaire with a Likert scale which was processed using Microsoft Excel 2007 software and SPSS Version 26 software. The data analysis used is correlation and multiple linear regression analysis. The results of this study indicate that Work Environment has a positive and significant effect on Organizational citizenship behavior, Organizational Commitment has a positive and significant effect on Organizational citizenship behavior, Emotional intelligence has a positive and significant effect on Organizational citizenship behavior, and Work Environment, Organizational Commitment, and Emotional intelligence simultaneously have a positive and significant effect on Organizational citizenship behavior.